Absence of maternal-fetal adverse effects of Alternanthera littoralis P. Beauv. following treatment during pregnancy in mice - Rezende, Giovana Corbucci Danti; Noronha, Renata Coelho Rodrigues; Ortiz, Hudman Cunha; do Nascimento, Luís Adriano Santos; das Neves, Silvia Cordeiro; Ventura Said, Yasmin Lany; Cardoso, Adauto Lima [UNESP]; de Mescouto, Vanessa Albuquerque; Vilela, Marcelo Luiz Brandão; do Nascimento, Valter Aragão; Coelho, Henrique Rodrigues Scherer; Leite Kassuya, Candida Aparecida; et al. (Taylor & Francis, 2023)
Alternanthera littoralis P. Beauv is a plant native to Brazil that exhibits various beneficial activities including antioxidant, antibacterial, antifungal, antiprotozoal, anti-hyperalgesic, and anti-inflammatory properties. The aim of this study was to assess the impact of the ethanol extract of Alternanthera littoralis (EEAl) on reproductive outcomes, embryofetal development, and DNA integrity of pregnant female mice. Pregnant Swiss female mice were randomly assigned to three experimental groups (n = 10): controls were administered either 1% Tween 80 (vehicle), EEAl 100 mg/kg or EEAl 1000 mg/kg. Treatment was administered through gavage during the gestational period until day 18. On gestational days 16, 17, and 18, a peripheral blood sample from the tail vein was obtained for DNA integrity analysis (micronucleus test). After the last collection, animals were euthanized by cervical dislocation. Maternal organs and fetuses were collected, weighed, and subsequently analyzed. Reproductive outcome parameters were assessed by measurement of number of implants, live fetuses, and resorptions. Embryonic development was determined by adequacy of weight for gestational age as well as determination of external, visceral, and skeletal malformations. Data demonstrated that EEAl did not produce maternal toxicity at either dose associated with no marked alterations in any of the reproductive outcome parameters including implantation sites, live/dead fetuses ratio, fetal viability, post-implantation losses, resorptions, and resorption rate. However, EEAl 1000 group reduced embryofetal development by lowering placental weight. In addition, there was an increase in the frequency of external and skeletal malformations in the EEAl 1000 group, which could not be attributed to extract exposure as these values were within control levels. Based upon our findings, evidence indicates that the EEAl at the concentrations employed in our study may be considered safe for use during pregnancy and extracts of this plant show potential for development of phytomedicines to be used in pregnancy.
Keywords: DNA damage; medicinal plants; mutagenesis; teratogenesis